2022
DOI: 10.3390/microorganisms10010148
|View full text |Cite
|
Sign up to set email alerts
|

Human MAIT Cells Respond to Staphylococcus aureus with Enhanced Anti-Bacterial Activity

Abstract: Mucosal-Associated Invariant T (MAIT) cells have been shown to play protective roles during infection with diverse pathogens through their propensity for rapid innate-like cytokine production and cytotoxicity. Among the potential applications for MAIT cells is to defend against Staphylococcus aureus, a pathogen of serious clinical significance. However, it is unknown how MAIT cell responses to S. aureus are elicited, nor has it been investigated whether MAIT cell cytotoxicity is mobilized against intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…MAIT cells can be activated in two distinct manners, TCR dependent activation via MR1 presentation of microbial antigens or TCR independent activation via cytokines such as IL-18 (7,11). Upon activation, MAIT cells can rapidly produce a wide range of cytokines and lytic molecules including interferon (IFN)g, interleukin(IL)-17 and granzyme B, which supports MAIT cell host defensive responses (12)(13)(14)(15). Several studies have demonstrated that MAIT cells can lyse both bacterially infected cells and transformed malignant cells in an MR1 dependent manner (14)(15)(16).…”
Section: Mait Cell Basicsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAIT cells can be activated in two distinct manners, TCR dependent activation via MR1 presentation of microbial antigens or TCR independent activation via cytokines such as IL-18 (7,11). Upon activation, MAIT cells can rapidly produce a wide range of cytokines and lytic molecules including interferon (IFN)g, interleukin(IL)-17 and granzyme B, which supports MAIT cell host defensive responses (12)(13)(14)(15). Several studies have demonstrated that MAIT cells can lyse both bacterially infected cells and transformed malignant cells in an MR1 dependent manner (14)(15)(16).…”
Section: Mait Cell Basicsmentioning
confidence: 99%
“…Upon activation, MAIT cells can rapidly produce a wide range of cytokines and lytic molecules including interferon (IFN)g, interleukin(IL)-17 and granzyme B, which supports MAIT cell host defensive responses (12)(13)(14)(15). Several studies have demonstrated that MAIT cells can lyse both bacterially infected cells and transformed malignant cells in an MR1 dependent manner (14)(15)(16). MAIT cells can also be activated independent of their TCR via innate cytokines, the best described being IL-12, IL-18 and type 1 interferons (11,(17)(18)(19)(20).…”
Section: Mait Cell Basicsmentioning
confidence: 99%
“…Co-culture of MAIT and dendritic cells infected with S. aureus enhances IFN-γ and granzyme B production and degranulation. Granzyme B has direct anti-staphylococcal activity and promotes neutrophil-mediated clearance of SA infected cells, reducing intracellular persistence of S. aureus ( Cooper et al., 2022 ). Hence, vitamins and MAIT may play a key role in resolving S. aureus infections.…”
Section: Immune Responses and Vitaminsmentioning
confidence: 99%
“…Mucosal Associated Invariant T (MAIT) cells are a population of unconventional T cells which are important in the immune defence against bacterial and viral infections 1, 2, 3, 4, 5, 6 . MAIT cells are restricted by the MHC-like molecule MR1 5 , and recognise a limited set of bacterially derived antigens 7 .…”
Section: Introductionmentioning
confidence: 99%